Using Moss Walls for Air Quality Monitoring: Extending Their Utility Beyond Traditional Green Infrastructure - Gana Gecheva; Zhana Petkova; Stoyan Damyanov; Deyana Georgieva; Vesselin Baev; Mariyana Gozmanova; Elena Apostolova-Kuzova; Galina Yahubyan (International Journal of Plant Biology, 2025)
Moss walls are acknowledged, though not widely, for their urban environmental benefits: humidity control, noise reduction, and air filtration. In this pioneering study, three outdoor living moss walls were installed in separate urban green spaces in Plovdiv, Bulgaria. One and five months later, the primary moss species used, Hypnum cupressiforme, a well-established biomonitor, was analyzed for 12 potentially toxic elements. The content of all measured elements increased, with zinc (Zn) and cadmium (Cd) showing the most significant rises—17-fold and 3-fold, respectively. The element accumulation is believed to originate from industrial activities related to non-ferrous metals. In addition to accumulating toxic elements, the moss exhibited physiological responses to environmental stress. Total lipids and tocopherols, lipophilic antioxidants produced exclusively by photosynthetic organisms, showed adaptive changes. As a molecular biomarker, the expression of the rbcL gene, which encodes the largest subunit of Rubisco, was analyzed, and showed a correlation with the Ecological Risk Index derived from the moss wall data. While living moss walls have been used to some extent to enhance urban aesthetics and improve air quality, this study is the first to highlight their potential as tools for air quality monitoring.